Managerial succession and firm performance - Huson, Mark R.; Malatesta, Paul H.; Parrino, Robert (Journal of Financial Economics, 2004)
We examine CEO turnover and firm financial performance. Accounting measures of performance relative to other firms deteriorate prior to CEO turnover and improve thereafter. The degree of improvement is positively related to the level of institutional shareholdings, the presence of an outsider-dominated board, and the appointment of an outsider (rather than an insider) CEO. Turnover announcements are associated with significantly positive average abnormal stock returns, which are in turn significantly positively related to subsequent changes in accounting measures of performance. This suggests that investors view turnover announcements as good news presaging performance improvements.